FAKTOR PENENTU HOLDING PERIOD SAHAM LQ-45 DI BURSA EFEK INDONESIA - Visita Yales Arma (Journal of Business & Banking, 2013)
Holding periods is the period of time during which one owns a security. In addition, holding period is influenced by transaction cost, market value, and risk. The objective of this research is to analyze the effect of bid-ask spread, market value, and variance return on holding period. The analysis of the data was done by multiple regression analysis. Using the data from 34 companies in LQ-45 index period 2010-2011, the results show that market value has positive effect and variance return has negative effect on holding periods. Theresults also show that Bid-Ask spread has no significant effect on holding periods. Investors will hold long position on securities that having higher market value and short position on securities that having higher risk.